The Impact of Eggshell Colour on the Quality of Table and Hatching Eggs Derived from Japanese Quail - Kamil Drabik; Justyna Batkowska; Kostiantyn Vasiukov; Adrian Pluta (Animals, 2020)
The aim of the study was to evaluate table and hatching eggs of Japanese quails (Coturnix coturnix japonica) depending on the eggshell colour. The research was carried out in two stages, in terms of table eggs’ quality and their biological value as hatching eggs depending on the eggshell colour. In both stages, 300 Japanese quail eggs were used in each (600 in total) divided into two equal groups: with a brown-spotted shell, with a uniform shell in shades of blue. In the 1st stage, quality characteristics of the whole egg (weight, specific gravity, proportions of particular elements), yolk (weight, colour, index), albumen (weight, height) and shell (colour, strength, weight, thickness, density) were evaluated. In the 2nd stage, eggs were incubated under standard conditions and following biological characteristics were analyzed: eggs fertility, embryo mortality, hatchability of fertile and set eggs, body weight of hatchlings and their proportion in egg weight. The shell colour, “blue” or spotted, of Japanese quail eggs, does not appear to influence their quality if they are intended for consumption. However, the hatching results and body weight of obtained chicks of Japanese quail may be affected by the eggshell colour.